The Effect of Subsidizing Continuous Training Investments - Evidence from German Establishment Data - Katja Görlitz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper evaluates the impact of a training voucher program on establishments' investments in further training. The voucher program that was implemented in the German federal state of North Rhine-Westphalia increased training incentives for employees in small and medium-sized establishments by reducing training costs by 50%. The estimation is based on a quasi-experimental research design exploiting variation across time, regions and establishment size. Using establishment data, I find that the share of establishments that invest in training increased by approximately 5 percentage points. Training intensity and the educational structure of participants remained unaffected among those establishments investing in training.
Keywords: J24; H25; 330; Continuous training; employers; training voucher; subsidies; difference-in- difference; Weiterbildung; Voucher; Subvention; Wirkungsanalyse; Betriebliche Weiterbildung; Bildungsinvestition; Nordrhein-Westfalen; Deutschland